Solar activity as a potential factor for foreshadowing drought in Indian summer monsoon regime (MAUSAM, 1981)
An attempt bas been made to determine Influence o solar activity on drought incidence in India, 100 year's rainfall (1875-1974) for northwest and peninsular India, have been analysed with respect to sunspot numbers and Baur's solar index and their distribution during drought years determined. Frequency of drought per cycle of solar activity have been obtained. Association between drought and maximum/minimum spottedness was tested by chi-square technique. Correlation have been computed between sunspots, Baur's index and rainfall during different phases of solar activity. The results revealed that on an average drought occures once in a solar cycle. Occurrence of maxima or minima did not have any relationship with the drought, which was found to occur earlier as well as later than either of the epochs, Correlation analysis revealed that for the Peninsula, sunspots numbers and its values during middle of the waxing phase were significant. The Baur's index bears significant correlation with northwest Indian rainfall. It's value during the waxing phase as also during middle of waxing phase is also significantly correlated with northwest Indian rainfall. The index was significant for peninsula rainfall during middle of waxing phase.